Pengaruh Lingkungan Kerja dan Kompensasi terhadap Disiplin Kerja dengan Loyalitas Karyawan sebagai Variabel Moderasi pada Generasi Milenial - Mira Feby Setiana; Fereshti N. Dihan (Lembaga Pengembangan Kinerja Dosen, 2025)
Important factors influencing employee work discipline are the work environment and compensation, especially among the Millennial Generation, which now dominates the workforce. Although known for their flexibility, Millennials demonstrate a high level of professionalism and work responsibility. Furthermore, employee loyalty serves as a moderating variable that strengthens the influence of compensation on work discipline. Therefore, a thorough understanding the characteristics, expectations, and loyalty of the Millennial Generation is crucial for organizations in building sustainable work discipline. Purpose of this study is to analyze the influence of the work environment and compensation on work discipline, with employee loyalty as moderating variable for the Millennial Generation. The research subjects were Millennial employees working in the formal sector, with a sample size of 200 respondents using a purposive sampling technique. A quantitative approach using explanatory research methods conducted in the following study, and data analysis was conducted using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results of the hypothesis testing indicate that the work environment and compensation have a positive and significant effect on work discipline. In addition, employee loyalty has been shown to strengthen influence of the work environment and compensation work discipline. This finding indicates that the higher the employee loyalty, the greater positive impact of the work environment and compensation improving work discipline. In conclusion, companies need to optimally manage the work environment and compensation system and foster loyalty to maintain and improve the discipline of millennial employees, which ultimately has a positive impact on organizational performance.